The Representation of Hadith in Muslim Wedding Culture: A Case Study of a Sharia Wedding Organizer in Indonesia - Alya Azzahra Salsabila (PT. Nawa Edukasi Nusantara, 2026)
This study examines the representation of Hadith in contemporary Muslim wedding culture through the practices of a Sharia Wedding Organizer (WO), focusing on Sakinah Walimah Syar’i in Yogyakarta, Indonesia. Employing a qualitative descriptive approach, this research analyzes Instagram content and service practices offered by the organizer. The findings reveal that Hadith is not merely cited as a normative religious reference but is performatively embodied in concrete service systems, such as gender-segregated wedding arrangements (walimah infishal), Sharia-compliant bridal makeup without prohibited bodily modifications, and the elimination of music during wedding receptions. This phenomenon reflects a process of living Hadith, in which textual authority transforms into a cultural instrument shaping social norms and collective religious identity. Furthermore, the study highlights the decentralization of religious authority in the digital era, the sacralization of public space, and the emergence of religious symbolic capital among urban Muslims. In this context, Sharia Wedding Organizers function not only as service providers but also as agents of religious meaning production, contributing to the transformation of Muslim wedding culture in contemporary Indonesia.